A survey on nursing and midwifery students’ viewpoints about factors related to effective clinical teaching in Semnan Azad University - Arfaie, katayoon; Sadegh Dolagh, khadijhe; Tondro, haneeh; Arastooee, zeynab (Advances in Nursing & Midwifery, 2011)
Abstract Background and aim clinical teaching provides a unique opportunity for learning professional skills. In order to be effective it needs enough equipments, correct communications and precise educational planning. It is clear that any deficiencies in this procces have negative consequences. Assessing students’ point of view about clinical teaching can provide useful insights for development.The purpose of this study was to assess nursing and midwifery students’ point of view about effective clinical teaching in Semnan Azad University in 2009. Materials and methods In this descriptive study, a total number of 160 nursing and midwifery students, studying at Semnan Azad University participated. The sampling was done through census. For collecting data a questionnaire was used. The questionnaire consisted of two sections. The first section assessed demographic variables and second part was designed to assess students’ perception of effective clinical teaching and related factors. Validity of questionnaire was assessed by content validity (panel of experts) and reliability was determined by calculating Cronbach alph with a coefficient of 0.90. The data were analyzed using SPSS software. Findings The majority of students were studying in third semester (58.1%) and were midwifery students and (41.9%) were nursing students. According to our participants point of view learner’s personal characteristics domain (24/35±3/6) and learning environment (16/36±2/94) were the most and the least important factors related to effective clinical teaching. in overall expert clinical teacher had the main role in effective clinical teaching. Conclusion With regard to what were found in this study ,the most important factors for learning of professional skills is interest and motivation, so education system should support this internal feelings and find the methods that prevent these drives. Keywords: Clinical teaching, nursing, midwifery, effective teaching